Choice Shift and Group Polarization - Friedkin, Noah E. (American Sociological Review, 1999)
I extend the theoretical domain of sociology into an area of social psychology that heretofore has been the exclusive domain of psychologists. Specifically, I develop a social structural perspective on the choice shifts that individuals make within groups. During interpersonal discussions of issues, choice shifts occur when there is a difference between group members’ mean final opinion and their mean initial opinion. Explanations of choice shifts have emphasized group-level conditions (e.g., a norm, a decision rule, a pool of persuasive arguments, a distribution of initial opinions). I argue that choice shifts are a ubiquitous product of the inequalities of interpersonal influence that emerge during discussions of issues. Hence, I bring choice shifts squarely into the domain of a structural social psychology that attends to the composition of networks of interpersonal influence and into broader sociological perspectives concerned with the formation of status structures.